Social Value Representation in Popular Balinese Love Song Lyrics: A Sociopragmatic Analysis - Suari Agung (Soshum: Jurnal Sosial dan Humaniora, 2026)
This study examines the forms and sociocultural functions of implicature in popular Balinese love song lyrics performed by Dek Ulik, focusing on four songs: Tiang Demen, Beli Sayang, Boya Je Alpaka, and Ratih Kamajaya. Employing a descriptive qualitative design with a sociopragmatic orientation, the study applies content analysis to song lyrics as cultural discourse. Data consist of words, phrases, clauses, and lyric lines containing implicature, analysed through pragmatic matching techniques grounded in implicature theory proposed by Grice (1975), politeness principles by Geoffrey Leech (2016), and the sociopragmatic framework of Jacob L. Mey (2021). The findings reveal that both conventional and conversational implicatures are employed to convey romantic meanings indirectly; however, conversational implicatures predominate (82%), while conventional implicatures account for 18%. Indirectness is realised through mitigation strategies, conditional expressions, rhetorical questioning, metaphorical references, and culturally shared symbolism. These pragmatic mechanisms encode socio-cultural values such as politeness, loyalty, filial respect, emotional restraint, and spiritual commitment. Such patterns reflect characteristics of high-context communication, where meanings are often implied to maintain interpersonal harmony. The study demonstrates that Balinese popular love songs function not merely as entertainment but as cultural texts that negotiate romantic relationships within local moral, familial, and spiritual frameworks. The novelty of this research lies in highlighting implicature as a sociocultural mechanism through which romantic discourse in Balinese popular music articulates culturally grounded relational values.